2003
DOI: 10.1590/s0066-782x2003001000002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between turbidimetric and nephelometric methods of measuring C-reactive protein in patients with unstable angina or non-ST elevation acute myocardial infarction

Abstract: Inflammation plays an important role in the atherosclerotic process 1 , and C-reactive protein (CRP) as an index of low-grade inflammation has been established as an independent predictor of cardiovascular events both in healthy individuals 2 and in patients with acute coronary syndromes (ACS) 3 . In stable individuals, values of CRP exceeding 0.3 mg/ dL are associated with a high risk of cardiovascular events 4 . Therefore, a highly sensitive method, such as nephelometry, is necessary to discriminate among su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…There are several laboratory techniques to measure CRP including nephelometry, turbidimetry and radial immunodiffusion or electroimmunodiffusion. The studies included in this review that described the CRP method used either nephelometry or turbidimetry, which seem to correlate well 24 . Although some interlaboratory variation may be expected, this is unlikely to be of clinical significance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are several laboratory techniques to measure CRP including nephelometry, turbidimetry and radial immunodiffusion or electroimmunodiffusion. The studies included in this review that described the CRP method used either nephelometry or turbidimetry, which seem to correlate well 24 . Although some interlaboratory variation may be expected, this is unlikely to be of clinical significance.…”
Section: Discussionmentioning
confidence: 95%
“…The studies included in this review that described the CRP method used either nephelometry or turbidimetry, which seem to correlate well. 24 Although some interlaboratory variation may be expected, this is unlikely to be of clinical significance. Highsensitivity CRP (hs-CRP) test is a novel type of CRP, which has significantly lower limits of detection (range 0.5-10 mg/l) and is most often used to help predict a healthy person's risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…If CRP is higher than 3 mg/l, a person is at high risk of developing cardiovascular disease, the risk is average between 1 and 3 mg/l and below 1 mg/l the risk is low (Kushner and Sehgal, 2002). CRP is nowadays diagnosed with tests like enzyme-linked immunoassay, nephelometric and turbidimetric assays (Correia et al, 2003). As new detection methods piezoelectric microcantilevers (Lee et al, 2004, Wee et al, 2005 and a microfluidic network (Wolf et al, 2004) has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature which compared the results of different spesific proteins, such as CRP, IgA, IgG, IgM, C3, C4, haptoglobin, transferin, apolipoproteins, RF etc. held by nefelometric and turbidimetric methods, and results of two methods were found to be correlated with each other [21,[28][29][30][31][32]. Correia et al [28] found that CRP levels measured by either methods were correlated with each other, in both unstable angina patients and in patients with non-ST elevation acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 96%
“…held by nefelometric and turbidimetric methods, and results of two methods were found to be correlated with each other [21,[28][29][30][31][32]. Correia et al [28] found that CRP levels measured by either methods were correlated with each other, in both unstable angina patients and in patients with non-ST elevation acute myocardial infarction. In Dominici et al [30] study, the two systems were found to perform substantially equally, both in hsCRP and in CRP measurement; but in the hsCRP assay, the precision of nephelometry (CV% in the interval 3.0-5.8) was lower than that of turbidimetry (CV% in the interval 1.8-2.3).…”
Section: Discussionmentioning
confidence: 96%